A preliminary analysis of renal infiltrating cells in acute tubular injury induced by water treated with high fluoride and high hardness in rat model - Perera, Thanusha; Ranasinghe, Shirani; Alles, Neil; Daniel, Christoph; Waduge, Roshitha (Research Journal of Biotechnology, 2021)
The impact of water containing high fluoride and high hardness on kidneys of rats was investigated. Control and test water sample with high fluoride and hardness were collected from Kandy and Mihinthale regions respectively. Twelve rats were divided into 2 control and 2 test groups. One set of control and test group received normal and test water for 60 days and the other set of control and test group received same water treatment for 90 days. Rats treated with test water for 60 days were observed loss of brush border in less than 25% of tubular cells and in 90 days associated with loss of brush border in more than 25% of tubule cells resulting in acute tubular injury compared to control group. Immunohistochemical staining revealed the strong infiltration of CD3 T-cells and CD68 macrophages in test group for 90 days.
CRIS-Team WoS Importer:2021-04-02